Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Inka Koch; Reinhard Drews; Steven Franke; Daniela Jansen; Falk Marius Oraschewski; Leah Sophie Muhle; Vjeran Višnjević; Kenichi Matsuoka; Frank Pattyn; Olaf Eisen (Journal of Glaciology)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.